2020
DOI: 10.1177/1120672120920537
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of micronutrient supplementation for reducing the risk of wet age-related macular disease and diabetic retinopathy

Abstract: Age-related macular disease and diabetic retinopathy are chronic degenerative diseases characterised by progressive visual impairment. In Europe, age-related macular disease accounts for over 15% of blindness in adults over 50 years of age, and although the burden of diabetic retinopathy in terms of vision impairment is lower, vision loss associated with diabetic retinopathy is increasing with the rising prevalence of diabetes mellitus and the ageing of the population. Late-stage age-related macular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 108 publications
(277 reference statements)
0
8
0
Order By: Relevance
“…Although eggs contain markedly less lutein than dark-green leafy vegetables, lutein bioavailability from eggs is higher than that from https://doi.org/10.1017/S0007114522002161 Published online by Cambridge University Press other food sources, possibly owing to the presence of the lipid matrix in egg yolk. 36 In a crossover trial, Chung et al observed that lutein-enriched egg consumption led to the highest serum lutein response compared with lutein supplements and spinach. 37 In addition, the influence of egg consumption on the incidence of AMD may be potentially mediated by other nutrients and compounds in the diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although eggs contain markedly less lutein than dark-green leafy vegetables, lutein bioavailability from eggs is higher than that from https://doi.org/10.1017/S0007114522002161 Published online by Cambridge University Press other food sources, possibly owing to the presence of the lipid matrix in egg yolk. 36 In a crossover trial, Chung et al observed that lutein-enriched egg consumption led to the highest serum lutein response compared with lutein supplements and spinach. 37 In addition, the influence of egg consumption on the incidence of AMD may be potentially mediated by other nutrients and compounds in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the inverse association was suggested to be stronger for the additive intakes of spinach and egg in the joint analysis. Although eggs contain markedly less lutein than dark-green leafy vegetables, lutein bioavailability from eggs is higher than that from other food sources, possibly owing to the presence of the lipid matrix in egg yolk (36) . In a crossover trial, Chung et al observed that lutein-enriched egg consumption led to the highest serum lutein response compared with lutein supplements and spinach (37) .…”
Section: Egg Intakementioning
confidence: 97%
“…Furthermore, its seems that gut microbiota may affect the metabolism of polyphenols to influence their bioactivity (Rowland et al, 2018). Finally, human and animal studies have underlined that gut microbiome composition may be influenced by several dietary nutrients such as omega-3 polyunsaturated fatty acids, which along with other nutrients (Costantini et al, 2017) are involved in ARMD (Rinninella et al, 2018;Battaglia Parodi et al, 2020).…”
Section: Gut-eye Axis and Retinal Diseasesmentioning
confidence: 99%
“…One molecule is represented by arimoclomol, which upregulates heat shock proteins protecting against neurodegeneration in amyotrophic lateral sclerosis and retinitis pigmentosa [90]. Furthermore, the oxidative stress contributing to neurodegeneration can also be targeted using antioxidants and micronutrient supplementation [91,92]. The use of nutritional supplements containing antioxidants and omega 3 fatty acids in type 2 diabetes significantly reduced the oxidative load, increasing circulating antioxidants [93].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%